Juridical Review of Criminal Liability Perpetrators of the Obstruction of Justice in Office Order - Putri, Pamuka Aisyah Perico; Basrawi, Basrawi; Sakti, La Ode Awal; Irabiah, Irabiah (Sangia Nibandera Law Research, 2024)
An official order is an order given by someone who has power and position in an institution or institution. A valid official order is an official order given by someone who has the authority and the order is still in the realm of his work. The article governing official orders is contained in Article 51 of the Criminal Code. Obstruction of justice is an act that harms many parties, therefore anyone involved in obstruction of justice deserves to be punished according to applicable law. The research method used in writing this thesis is normative, namely examining laws and examining scientific papers that are in accordance with the problems that are the topic of making a thesis. The result of this research is that a person who commits an act of obstruction of justice in an official order can be given a penalty according to the provisions if with full awareness knows that the act is an act that has elements of a criminal offense and cannot be said to be obstruction of justice if the person concerned does not know at all that the order contains elements of a criminal offense.